Product Development Using Quality Conversion Technique in the Health Industry Srinagarind Hospital With the Design of 3D Automatic Transportation Vehicles - Kanoksirirujisaya, Nunthaphan; Poonikom, Kanisorn (Princess of Naradhiwas University Journal, 2021)
This study was a research and development aiming at suggesting guidelines on the design and development of 3D automatic transport vehicles used in the clinical laboratories of Srinagarind Hospital. As staff must deliver specimens over long distances per day, this resulted in fatigue and time-consuming transport. As a result, the design of the vehicles applied Quality Function Development (QFD) technique by holding a meeting of stakeholders including the registration and the clinical laboratory staff to find a design specification that could meet their needs. The analysis led to the design that could be suggested to experts. The results of research indicated that the prototype of the automatic transport vehicles suited the staff’s needs and decreased the amount of time spent on delivery from 8 minutes to 3 minutes. .